Peran Aktivitas Fisik Harian dalam Mengendalikan Komplikasi Hipertensi pada Lansia : Studi Kasus - Fatih Hibatullah (Sekolah Tinggi Ilmu Kesehatan Sapta Bakti, 2026)
One of the main health problems for the elderly is hypertension, which has the potential to cause many cardiovascular complications. According to research, daily physical activity is very important for controlling blood pressure and reducing the risk of complications. The aim of this study is to see how daily physical activity correlates with the level of hypertension complications in the elderly. This study was designed using a cross-sectional observational analytical approach. The results showed that elderly people who are less active have a higher risk of hypertension complications compared to more active elderly people. The results indicate that daily physical activity is a non-pharmacological way to control hypertension in the elderly.